Wykonaj mnożenie i redukcję wyraów podobnych !

5a + 4 (a-1) =

5a + 3 (a-2) +5b =

4 (2b + ½ )- 6b =

2a + 0,5 (a-2) + 5b =



Przekształć wyrażenia na sumę i wykonaj redukcję wyrazów podobnych ! :/



6 (2a - 6b + 3c) =

(3x - 2y + 9) * 4 =

3 (5x - 8z - 2) =

(4x - 7y - 7) (-2) =

-8 (7n + 9p+ t ) =

-2 (3a + 1) + (4a - 5) =

3

Odpowiedzi

2010-02-09T17:45:33+01:00
5a +4a-4= 9a-4
5a+3a-6+5b=8a-6+5b
8b+2-6b= 2b+2
2a+0.5a-1+5b= 2.5a-1+5b



12a-6b+18c
12x-8y+36
15x-32z-6
-8x+14y+14
-56n-72p-8t
3 3 3
2010-02-09T17:46:04+01:00
Wykonaj mnożenie i redukcję wyraów podobnych !
5a + 4 (a-1) =5a+4a-4=9a-4
5a + 3 (a-2) +5b =5a+3a-6+5b=8a+5b-6
4 (2b + ½ )- 6b =8b+2-6b=2b+2
2a + 0,5 (a-2) + 5b =2a+0,5a-1+5b=2,5a+5b-1

Przekształć wyrażenia na sumę i wykonaj redukcję wyrazów podobnych ! :/

6 (2a - 6b + 3c) =12a-36b+18c

(3x - 2y + 9) * 4 =12x-8y+36

3 (5x - 8z - 2) =15x-24z-6

(4x - 7y - 7) (-2) =-8x+14y+14

-8 (7n + 9p+ t ) =-56n-72p-8t

-2 (3a + 1) + (4a - 5) =-6a-2+4a-5=-2a-7
2 5 2
2010-02-09T17:48:31+01:00
1)5a+4a-4=9a-4
2)5a+3a-6+5b=8a+5b-6
3)8b+2-6b=2b+2=2(b+1)
4)2a+½a-1+5b=2½a+5b-1
5)12a-36b+18c
6)12x-8y+36
7)15x-24z-6
8)-8x+14y+14
9)-56n-72p-8t
10)-6a-2+4a-5+-2a-7
2 3 2